Assessment of stent optimization in clinical practice using optical coherence tomography: a multicentric observational study. (14th October 2021) - Rai, H; Harzer, F; Raeber, L; Leistner, D M; Alfonso, F; Xhepa, E; Nef, H; Laugwitz, K L; Byrne, R A; Kastrati, A; Joner, M
Abstract: Background: Stent under-expansion obtained at the time of percutaneous coronary intervention (PCI) has been shown to be associated with worse outcomes. Purpose: We sought to define OCT assessed optimal stent expansion index which associates with lower incidence of major adverse cardiac events (MACE) during follow-up in a sample of patients stented at five high volume centers of central Europe. Methods: We analyzed 370 lesions stented during the period between 2012 and 2018, with their final procedural results imaged using optical coherence tomography (OCT). QIvus Research Edition v3.1 (Medis, Leiden, NL) was used for OCT analysis. The stented segment was split in two equal halves. Stent expansion index (SEI) was calculated for both halves separately by dividing minimum stent area by the mean reference lumen area [(proximal reference area + distal reference area)/2]. Smallest of the two prevailed as the SEI of that case. MACE during post-PCI follow-up was defined as composite of all-cause death, myocardial infarction, stent thrombosis and target lesion revascularization. Data is expressed as mean±SD or median (Interquartile range). Incidence of subsequent MACE is expressed as crude rates (%). Results: A total of 316 cases (370 lesions), aged 64.6±11.7 years were included for OCT analysis. Of them, 78.8% were males, 22.8% were diabetics, 75.9% were hypertensives while 35.1% had family history of coronary artery disease. 38.0% of the cases had acute coronary syndrome at presentation. 62.4% of treated lesions were complex (Type B2/C). A mean of 1.11±0.34 stents/scaffolds were implanted per treated lesion. Analyzed segment length was 20.4 (15.17, 27.0) mm. Minimal stent area (MSA) in the overall stented segment was 6.02 mm 2 (4.65, 7.93). Median stent expansion index (minimum) was 0.79 (0.71, 0.86). Median follow-up duration was 557 days (326, 1, 096). 47 lesions (12.7%) suffered MACE during follow-up. Receiver operating characteristic (ROC) curve analysis using Youden's rule identified 0.84 as SEI cut-off powered to predict post-PCI MACE (AUC= 0.60, sensitivity= 0.85, specificity= 0.34). MACE was observed in 38/249 (15.3%) of lesions with SEI≤0.84 and in 9/121 (7.4%) of lesions with SEI>0.84 (p=0.03). Univariate regression analysis of MACE revealed significant association with SEI≤0.84 (OR=2.2, 95% CI=1.1–4.8, p=0.04) Adaptive Lasso regression identified SEI≤0.84 (OR=4.1, 95% CI=1.3–12.6, p=0.02) and coronary calcification at baseline (OR=2.7, 95% CI=1.1–6.6, p=0.03) as independent predictors of MACE during follow-up. Kaplan-meier curve for MACE free survival with optimal SEI (n=121) and sub-optimal SEI (n=249) subgroups using SEI cut-off of 0.84, however showed modest separation (p=0.11). Conclusions: The present study identified SEI>0.84 associated with lower incidence of MACE as optimal cut-off in daily practice. Along with SEI of ≤0.84, coronary calcification was also significantly associated with MACE during post PCI follow-up. Funding Acknowledgement: Type of funding sources: None.